Influência da coca-cola® sobre a microdureza de resinas compostas nanohíbrida e bulk fill - Brugim, Luiz Henrique (2016)
The search for static restorative materials with better qualities has provided great technological development in the field of dental materials. The aim of this study was to evaluate the microhardness of composite Nanohybrid resin and Bulk fill when immersed in distilled water for 24 hours and Coca-Cola® or distilled water for 30 days. To this they were prepared 36 specimens of each composite and divided into 3 experimental groups (n = 12): I- storage in distilled water at 37 ° C for 24 hours, II - storage in distilled water at 37 ° C for 30 days and III - storage Coca-Cola® for 30 days. After the storage period the samples were subjected to the evaluation test of microhardness Knoop, with load of 50 kgf for 15 seconds. The results for each experimental condition were subjected to statistical analysis using the Kruskal-Wallis test, followed by Dunn post test, (p<0.05). The results demonstrated microhardness superior to Z350 resin compared to bulk fill resin, when immersed in distilled water for 24 hours and Coca-Cola® for 30 days. Already soaking in distilled water for 30 days, revealed no statistically significant differences between the two composite resins evaluated.